The primate remains from Roc de Santa (Late Eocene, NE Spain) revisited: New taxonomic allocation. Issue 121 (August 2018) - Minwer-Barakat, Raef; Marigó, Judit; Moyà-Solà, Salvador
Abstract: The scarce primate remains from the late Eocene locality of Roc de Santa (Central Pyrenees, NE Spain) were first documented in 1975. This material included a mandibular fragment with P3 -M2 and a maxillary fragment with P 3 -M 3 assigned to Adapis magnus (later transferred to the genus Leptadapis ), and an isolated M3 attributed to Necrolemur antiquus . However, these specimens were never described in detail. We have thoroughly studied these specimens, with the exception of the mandibular fragment, which has been lost. The maxillary fragment is much smaller than in Leptadapis magnus and shows clear morphological differences from that species; this specimen is assigned to Microchoerus hookeri . Similarly, the isolated M3 resembles that of M. hookeri in size and morphology, and can therefore be attributed to this taxon. In addition, we describe an upper incisor never reported previously, which can also be allocated to M. hookeri, representing the first description of this tooth for the species. Therefore, we conclude that the previous taxonomic determinations were mistaken and all the available primate specimens from Roc de Santa can be confidently assigned to the species M. hookeri, previously described from the same-age localities of Sossís, Spain, and Eclépens-B, Switzerland.